Implementation of The Free Nutritious Meal Program (MBG) in Support of SDGs Points 3 & 4 in Jayapura City - Vanny Efa Medlama; Roberto Oktavianus Cornelis Seba; Sri Suwartiningsih (Dinasti Publisher, 2026)
This article analyzes the implementation of the Free Nutritious Meals (MBG) Program to support the achievement of Sustainable Development Goals (SDGs) Points 3 (Healthy and Prosperous Life) and Point 4 (Quality Education) in Jayapura City. The MBG Program is a local government policy focused on meeting the nutritional needs of students to improve health and support the learning process. This study used a qualitative literature review approach, drawing on books, government publications, research findings, and published articles. The results highlight that the MBG program has been well implemented in Jayapura City and has had a positive impact on improving student nutritional status, as well as school attendance and concentration. These results support the achievement of SDGs Points 3 and 4. However, several challenges remain in its implementation, such as budget constraints, uneven food distribution, and a lack of supporting infrastructure. Therefore, improved coordination between sectors, increased resource allocation, and ongoing evaluation are needed to ensure the program's effectiveness.